Feeding practices and nutritional status of under-five children in a peri-urban setting in Ibadan, southwest Nigeria: a comparative cross-sectional study (2023)
Background: Existing literature suggests inequalities in nutritional and feeding practices for children in rural communities compared to their urban counterparts. However, with increasing urbanization and changing social norms, re-assessment of rural-urban differences in feeding practices for under-five children is essential. This study therefore aimed to assess the feeding practices and nutritional status of children in a peri-urban setting in Ibadan. Methods: We conducted a community-based cross-sectional comparative study in peri-urban LGA (Lagelu) in Ibadan. Participants were 617 caregivers of under five children identified, from wards typical of rural and urban settings, through a multistage sampling technique. Caregivers’ sociodemographic details, 24-hour dietary recall of the child’s feeding, and anthropometric measurements were obtained. Results: Nearly half of the children were 2 years or older (rural: n=142, 47.2%; urban: n=147, 46.2%). There was significant difference between settings in terms of maternal age and education, father’s education, caregiver’s occupation and socioeconomic status. In total, 611 children (99.0%) were breastfed. Of those breastfed, 45% and 39% in rural and urban settings respectively were initiated within an hour of delivery. Children in rural setting had longer duration of breast feeding. However, they are less likely to be exclusively breast fed for 6 – months compared with children whose caregivers are urban dwellers. Dietary diversity was similar in both settings but higher among males. (20.3% male, 11.7% female in rural; 17.3% male and 15.5% female in urban). Overall, 108 (22.3%), 107 (21.9%), 152 (30.6%) and 34 (7.0%) of children aged 6-59 months were cachetic, underweight, stunted, and overweight respectively but commoner among children in rural settings. Conclusion: Feeding and nutrition programmes need to apply a gender lens if sustained behavioural interventions on child nutrition are to reach equitable outcomes.